The effect of shade on leaf characteristics of Mikania micrantha (Compositae) and their influence on retention of Imazapyr - Ipor, Isa; Tawan, Cheksum (Universiti Putra Malaysia Press, 1995)
Shading led to changes in the leaf histological characteristics of Mikania micrantha H.B.X., leaves at higher light intensity being thicker than those at lower light intensity. There was a significant increase in the area of spread of imazapyr droplets and retention on the upper leaf surface at lower light intensity, suggesting that shading had changed the upper surface topography and the amount of epicuticular wax of the leaves.